2018
DOI: 10.1016/j.nicl.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Disruption to functional networks in neonates with perinatal brain injury predicts motor skills at 8 months

Abstract: ObjectiveFunctional connectivity magnetic resonance imaging (fcMRI) of neonates with perinatal brain injury could improve prediction of motor impairment before symptoms manifest, and establish how early brain organization relates to subsequent development. This cohort study is the first to describe and quantitatively assess functional brain networks and their relation to later motor skills in neonates with a diverse range of perinatal brain injuries.MethodsInfants (n = 65, included in final analyses: n = 53) w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 63 publications
5
39
0
1
Order By: Relevance
“…These results are similar to previous preterm studies that have found disrupted functional connectivity of sensorimotor networks in premature neonates (Linke et al, 2018) and in perceptual and motor networks more broadly in adults born preterm, including the sensorimotor, visual, and auditory networks . These results are similar to previous preterm studies that have found disrupted functional connectivity of sensorimotor networks in premature neonates (Linke et al, 2018) and in perceptual and motor networks more broadly in adults born preterm, including the sensorimotor, visual, and auditory networks .…”
Section: Patterns Of Aberrant Ongoing Brain Activity Fluctuationssupporting
confidence: 91%
See 1 more Smart Citation
“…These results are similar to previous preterm studies that have found disrupted functional connectivity of sensorimotor networks in premature neonates (Linke et al, 2018) and in perceptual and motor networks more broadly in adults born preterm, including the sensorimotor, visual, and auditory networks . These results are similar to previous preterm studies that have found disrupted functional connectivity of sensorimotor networks in premature neonates (Linke et al, 2018) and in perceptual and motor networks more broadly in adults born preterm, including the sensorimotor, visual, and auditory networks .…”
Section: Patterns Of Aberrant Ongoing Brain Activity Fluctuationssupporting
confidence: 91%
“…In addition to increased ALFF in thalamus, more widespread increases were found in the pre-and post-central gyri. These results are similar to previous preterm studies that have found disrupted functional connectivity of sensorimotor networks in premature neonates (Linke et al, 2018) and in perceptual and motor networks more broadly in adults born preterm, including the sensorimotor, visual, and auditory networks . Similar primary damage and secondary disease effects may explain these results.…”
Section: Patterns Of Aberrant Ongoing Brain Activity Fluctuationssupporting
confidence: 91%
“…In contrast, the frontoparietal network is still fragmented around birth and during the first year of life (Fransson et al, 2009;Gao et al, 2015;He and Parikh, 2016). Disruptions of the developing somatomotor and frontoparietal functional networks around term equivalent age has been recently linked to motor impairments in the first 4 -8 months of life (Linke et al, 2018). Combining these findings we observe that local development of the functional architecture of the brain before birth is dynamic and develops in a sequential primary to higher cognitive fashion (Gao et al, 2009;Doria et al, 2010;Smyser et al, 2010;Schöpf et al, 2012;Thomason et al, 2013van den Heuvel et al, 2015).…”
Section: Discussionmentioning
confidence: 59%
“…[8][9][10][11][12] Only one published study has correlated neonatal functional connectivity with later outcomes in infants with brain injury, finding that functional connectivity MRI predicted motor impairment at 4 and 8 months of age. 13 Our long-term goal is to determine whether DTI and fMRI can be used as an adjunct to conventional structural clinical MRI in the first few weeks after birth to add additional information for clinicians and families about potential damage to motor pathways. Our goal for this study was to evaluate the prognostic value of DTI and functional connectivity derived from task-based fMRI in infants with perinatal brain injury at <48 weeks' corrected age for motor outcomes at 2 years of age.…”
mentioning
confidence: 99%